Indicadores de calidad en la atención al cliente en una empresa de comida rápida que ofrece cinco servicios varios. - Ochoa Guncay, Mishelle Andreina (My University, 2020)
This work as part of the General test, a case study of audit of quality management system, proposed on the page of qualifications of accounting and auditing of the academic unit of business career was raised from the Universidad Técnica de Machala, to obtain the title of third level "Engineer in accounting and audit - CPA". Research that is divided into three parts: introduction, development and conclusion. In the introduction there is evidence of the history of the problem in customer service; the importance of the area as an essential part of the business in March; giving a novel approach to their research; proposed objective identify factor that originated the efficiency indicator gap in attention to the customer in the company's fast food Karcoso, for the determination of the cause in pursuit of satisfaction in the service; and the case in the measurement of satisfaction in the service was delimited customer through the audit of quality management systems. In case development, formulated as theoretical framework eight scientific articles related to the attention to the client and management audits, also presented definitions of key words, the problem was resolved, the respective analysis was made and is He presented discovery sheet, narrating the comment, conclusion and recommendation as part of the management review. At the end was raised three conclusions where the problem solved with the investigated theoretical framework is contrasted.
El presente trabajo como parte del examen complexivo, se planteó un caso práctico de auditaría de sistema de gestión de calidad, propuesto en la página de titulación de la Carrera de Contabilidad y Auditoría de la Unidad Académica de Ciencias Empresariales de la Universidad Técnica de Machala, para la obtención del título de tercer nivel “Ingeniera en Contabilidad y Auditoría–CPA”. Investigación que se encuentra dividida en tres partes: Introducción, desarrollo y conclusión. En la introducción se evidencia los antecedentes del problema en el servicio de atención al cliente; la importancia del área como parte esencial del negocio en marcha; dando un enfoque novedoso a lo investigado; se propuso como objetivo determinar los estándares de calidad y el nivel de satisfacción del cliente a través de los últimos cinco años, para la medición del grado de eficiencia; y se delimitó el caso en la medición de satisfacción en el servicio al cliente a través de la determinación de indicadores de calidad. En el desarrollo de caso, se formuló como marco teórico diez artículos científicos relacionados a la atención al cliente y sistema de gestión de calidad, además se presentó definiciones de las palabras claves, se resolvió el problema planteado, se hizo el análisis respectivo, narrando el comentario, y la recomendación. Al final se planteó dos conclusiones donde se contrastó el problema con el marco teórico.
Keywords: INDICADORES DE CALIDAD; EFICIENCIA; SERVICIO DE ATENCIÓN AL CLIENTE; SISTEMA DE GESTIÓN DE CALIDAD